The Determination Of The Relationship Between Vo2max And The Angiotensin-Converting Enzyme Gene (ACE) rs1799752 Polymorphisms In The Turkish National Ice Hockey Sports Team: Comparing ACE (rs1799752) and Vo2max Value - Sercan Doğan, Canan; Polat, Tolga; Akkoç, Orkun; Kurudirek, Muhammet İrfan; Ulucan, Korkut (Cellular and Molecular Biology, 2022)
In the present study, the effect of ACE rs1799752 polymorphism on maximal oxygen consumption (VO2max) in ice hockey players was analyzed. For this reason, 21 male National Ice Hockey players, aged between 18-25, were recruited for the study. The conventional polymerase chain reaction (PCR) was used on the genotype rs1799752 polymorphism. The VO2max values were calculated by using the 20m Shuttle Run tests. The numbers and percentages of the II, ID and DD genotypes were 9 (%43), 7 (%33), and 5 (%24), respectively. The allelic distribution for I and D alleles was found to be 25 (60%) and 17 (40%), respectively. The mean VO2max of all the athletes was calculated as 47.52 ml. The mean VO2max of the II, ID, and DD genotypes were 49.74ml, 47.34 ml, and 46.43 ml, respectively. We found that the oxygen utilization capacity increased from the DD genotype to the II genotype. However, this increase was not statistically significant (p> 0.05). In order to confirm our findings, it is recommended that larger prospective studies depending on the effect of the relevant polymorphisms needed to be carried out.